3D Assembly of Graphene Nanomaterials for Advanced Electronics. (27th March 2020) - Le Ferrand, Hortense; Chabi, Sakineh; Agarwala, Shweta
Abstract : Since the discovery of electricity and the creation of the first transistors two centuries ago, the field of electronics has evolved rapidly to become omnipresent. Today, electronic devices are challenged by new demands in function and performance: they are expected to be lightweight, highly efficient, flexible, smart, implantable, and so on. To meet these demands, the materials and components in devices need to be carefully selected and assembled together. In this regard, the controlled assembly of 3D graphene structures holds tremendous potential to achieve such levels of multifunctionality and outstanding properties. Advanced processing approaches, such as 3D printing, allow the fabrication of a variety of 3D graphene–based materials that present outstanding properties and a high degree of multifunctionality. Herein, the recent progress in the fabrication of graphene‐based devices for advanced electronics using controlled assembly is reported. The benefits of controlling the microstructure of graphene nanomaterials for enhanced properties and functionalities are highlighted, and the various fabrication methods and their implications on the organization of materials are reviewed, as well as selected electrical devices. The approaches described here are opening up new avenues for the fabrication of health or structural monitoring devices, autonomous machines, and interconnected objects. Abstract : Today's demands of multifunctional and high‐performance electronic devices challenge current materials. The controlled assembly of 3D graphene structures is a path for the fabrication of health or structural monitoring devices, autonomous machines, and interconnected objects. These methods comprise direct synthesis, magnetic manipulation, and 3D printing.